The glacial geomorphology of the Cordillera Darwin Icefield, Tierra del Fuego, southernmost South America - Eñaut Izagirre; Neil Glasser; Brian Menounos; Juan-Carlos Aravena; Sérgio Faria; Iñaki Antiguedad (Journal of Maps)
The Cordillera Darwin Icefield (CDI) has experienced widespread retreat since the Little Ice Age (LIA, ∼1870 AD). Prior to this, information on outlet glacier dynamics is limited as there are few terrestrial observations and little mapped deglacial evidence, limiting our understanding of CDI dynamics on Holocene centennial to millennial timescales. Here we present a glacial geomorphological map of terrestrial landforms and features for the CDI and surrounding areas of the Tierra del Fuego archipelago. We digitized more than 8,000 glacial landforms and features covering an area of ∼13,300 km2 from a combination of digital elevation models (DEMs) and high-resolution satellite and aerial imagery (<3 m), supported by multitemporal field mapping. This work provides a detailed geomorphological assessment for the area, summarized in a single map, that identifies three main glacial landsystem types of the Patagonian–Fuegian landscape: (i) upland glacier, (ii) lowland land-terminating, and (iii) glaciomarine fjord. The resulting map forms the basis for future chronological campaigns.